Neoliberalism in Crisis, Accumulation, and Rosa Luxemburg's Legacy - Zarembka, Paul (Research in political economy ;, 2004)
This volume of Research in Political Economy sets out to explore three key themes pertinent to the critique of political economy: (1) the disciplinary role of capital under neoliberalism, (2) accumulation and finance, and (3) the life and theories of Rosa Luxemburg. While the sections focus on different aspects of political economy, taken as a whole, they complement each other in striking a balance between concrete and abstract Marxist analyses. The essays in the first section critically examines the more concrete aspects of political economy, such as the changing role of the World Bank vis-a-vis the Third World, the Millennium Challenge Account - a newly forged 'official development compact' put forward by the Bush II administration, the disciplinary strategies tied to labour restructuring in Argentina, the political economy of financial fragility on a global scale, and a cultural critique of the Documenta11. The essays in the second section explore analytically dimensions of Marx's theory of the monetary circuit, Rudolf Hilferding's banking theory, Henryk Grossman's Law of Accumulation, and the evidence surrounding supposed value-price correlations. The articles in the third section of the volume are devoted to the person and theoretical contribution of Rosa Luxemburg, the famous Polish-German theoretician and revolutionary leader.